1992
DOI: 10.1093/nar/20.8.1967
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and localization of an RNA helicase gene from a human lymphoid cell line with chromosomal breakpoint 11q23.3

Abstract: A gene encoding a putative human RNA helicase, p54, has been cloned and mapped to the band q23.3 of chromosome 11. The predicted amino acid sequence shares a striking homology (75% identical) with the female germline-specific RNA helicase ME31B gene of Drosophila. Unlike ME31B, however, the new gene expresses an abundant transcript in a large number of adult tissues and its 5' non-coding region was found split in a t(11;14)(q23.3;q32.3) cell line from a diffuse large B-cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 32 publications
(34 reference statements)
0
52
0
Order By: Relevance
“…We found the following to be consistent observations in at least four batches each of oocyte and egg lysates; we show the results with one oocyte lysate and one egg lysate immunoprecipitated with antibodies from preimmune and three immune sera (Fig+ 1)+ As expected, in oocyte immunoprecipitates, p82/CPEB is a major silver-stainable band+ p92/CPEB is present in egg immunoprecipitated material (see the western in Fig+ 3), but the phosphorylated clam CPEB apparently silver stains with a lighter hue than its unmodified form+ In addition, several abundant or moderately abundant polypeptides specifically coprecipitated with CPEB, but not with preimmune IgG-coated beads+ In particular, a 47-kDa protein (p47) is coimmunoprecipitated in oocytes, but is absent from egg precipitates and from oocyte ones pretreated with RNase A+ Secondly, unlike p47, p60 is found in both oocyte and egg lysates, but its coprecipitation also requires RNA+ We also noted the presence of higher molecular weight polypeptides that specifically pelleted with immune IgG-bound beads, including one migrating at about 105 kDa+ We have thus discerned a variety of patterns of possible clam CPEB partners, whose changes in association and Figure 2 with the RCK/p54 family members including human RCK (Lu & Yunis, 1992), mouse p54 (Seto et al+, 1995), Xenopus Xp54 (Ladomery et al+, 1997), Drosophila ME31B (de Valoir et al+, 1991), C. elegans Cgh-1, Schizosaccharomyces pombe Ste13 (Maekawa et al+, 1994), and Saccharomyces cerevisiae Dhh1 (Strahl-Bolsinger & Tanner, 1993)+ The degree of homology between members FIGURE 1. Proteins that coimmunoprecipitate with clam p82/p92 in oocyte and egg lysates+ Proteins that coimmunoprecipitate with preimmune (PI) and three rabbit anti-p82 antisera (Rb 28, Rb 29, and Rb 30) covalently bound to protein A-Sepharose, from clam oocyte (o) and egg (e) lysates+ In indicated lanes, extracts were preincubated with RNAse A prior to immunoprecipitation (ϩ)+ Proteins were separated on a 15% polyacrylamide gel and detected by silver nitrate staining+ The positions of p82/CPEB, p47, p60, p105, and IgG are shown+ of the RCK helicase family is strikingly high throughout the helicase core, with differences being confined to the N and C termini+ Such variable extensions have been suggested in other helicases to mediate substrate specificity or subcellular localization; no obvious conserved RNA-binding or localization domains reside in these extensions+ The clam and Xenopus proteins share 77% of identical residues (85% homologous) whereas clam and the yeast proteins contain 68% identical (77% homologous) residues+ All of the sequences share the motifs typical of DEAD box helicases (Fig+ 2)+ During the course of cloning, a partial clone encoding clam eIF4A was also obtained and is included in the FIGURE 2.…”
Section: Identification Of Clam P82/cpeb Interacting Partners In Oocymentioning
confidence: 85%
“…We found the following to be consistent observations in at least four batches each of oocyte and egg lysates; we show the results with one oocyte lysate and one egg lysate immunoprecipitated with antibodies from preimmune and three immune sera (Fig+ 1)+ As expected, in oocyte immunoprecipitates, p82/CPEB is a major silver-stainable band+ p92/CPEB is present in egg immunoprecipitated material (see the western in Fig+ 3), but the phosphorylated clam CPEB apparently silver stains with a lighter hue than its unmodified form+ In addition, several abundant or moderately abundant polypeptides specifically coprecipitated with CPEB, but not with preimmune IgG-coated beads+ In particular, a 47-kDa protein (p47) is coimmunoprecipitated in oocytes, but is absent from egg precipitates and from oocyte ones pretreated with RNase A+ Secondly, unlike p47, p60 is found in both oocyte and egg lysates, but its coprecipitation also requires RNA+ We also noted the presence of higher molecular weight polypeptides that specifically pelleted with immune IgG-bound beads, including one migrating at about 105 kDa+ We have thus discerned a variety of patterns of possible clam CPEB partners, whose changes in association and Figure 2 with the RCK/p54 family members including human RCK (Lu & Yunis, 1992), mouse p54 (Seto et al+, 1995), Xenopus Xp54 (Ladomery et al+, 1997), Drosophila ME31B (de Valoir et al+, 1991), C. elegans Cgh-1, Schizosaccharomyces pombe Ste13 (Maekawa et al+, 1994), and Saccharomyces cerevisiae Dhh1 (Strahl-Bolsinger & Tanner, 1993)+ The degree of homology between members FIGURE 1. Proteins that coimmunoprecipitate with clam p82/p92 in oocyte and egg lysates+ Proteins that coimmunoprecipitate with preimmune (PI) and three rabbit anti-p82 antisera (Rb 28, Rb 29, and Rb 30) covalently bound to protein A-Sepharose, from clam oocyte (o) and egg (e) lysates+ In indicated lanes, extracts were preincubated with RNAse A prior to immunoprecipitation (ϩ)+ Proteins were separated on a 15% polyacrylamide gel and detected by silver nitrate staining+ The positions of p82/CPEB, p47, p60, p105, and IgG are shown+ of the RCK helicase family is strikingly high throughout the helicase core, with differences being confined to the N and C termini+ Such variable extensions have been suggested in other helicases to mediate substrate specificity or subcellular localization; no obvious conserved RNA-binding or localization domains reside in these extensions+ The clam and Xenopus proteins share 77% of identical residues (85% homologous) whereas clam and the yeast proteins contain 68% identical (77% homologous) residues+ All of the sequences share the motifs typical of DEAD box helicases (Fig+ 2)+ During the course of cloning, a partial clone encoding clam eIF4A was also obtained and is included in the FIGURE 2.…”
Section: Identification Of Clam P82/cpeb Interacting Partners In Oocymentioning
confidence: 85%
“…Dhh1p belongs to a highly conserved subfamily of DEAD box helicase termed RCK/p54 helicases after the human protein (Akao et al+, 1992;Lu & Yunis, 1992)+ Family members include Clam p47 (Minshall et al+, 2001), mouse p54 (Seto et al+, 1995), Xenopus Xp54 (Ladomery et al+, 1997), Drosophila Me31B (de Valoir et al+, 1991), Caenorhabditis elegans cgh-1 (Navarro et al+, 2001), and Schizosaccharomyces pombe Ste13 (Maekawa et al+, 1994)+ Several lines of evidence suggest that Dhh1p and other members of this family may play an important role in promoting mRNP remodeling during mRNA metabolism and decay+ Dhh1p was isolated as a high copy suppressor of both ccr4⌬ and pop2⌬ cells (Hata et al+, 1998)+ Although originally identified as transcription factors (Liu et al+, 1998), both Ccr4p and Pop2p have recently been shown to be components of the cytoplasmic deadenylase in yeast )+ Additionally, the yeast genomic two-hybrid analysis has identified possible interactions between the decapping enzyme, Dcp1p, and Dhh1p (Uetz et al+, 2000)+ Lastly, the Xenopus homolog of Dhh1p, Xp54, is a major component of stored maternal mRNA particles, suggesting this protein may be involved in translational control following deadenylation (Ladomery et al+, 1997)+ Taken together, these observations suggest Dhh1p may be important in mediating events following deadenylation, thereby promoting mRNA decapping and/or translational repression+…”
Section: Introductionmentioning
confidence: 99%
“…DDX6 and its homologs are thought to function in remodeling mRNPs so as to facilitate multiple aspects of mRNA metabolism, including transcription, splicing, translation, degradation, and storage (8,26). Human DDX6 was first identified as a 54-kDa protein encoded by a gene located at a chromosomal breakpoint in a cell line, RC-K8, derived from a B-cell lymphoma (hence its alternative name, Rck/p54) (28). It has been suggested to function as a proto-oncogene and is overexpressed in some colorectal cancers (14).…”
mentioning
confidence: 99%